High-Risk Indicators of Renal Involvement in Primary Sjogren’s Syndrome: A Clinical Study of 1002 Cases - Jing Luo; Yu-Wei Huo; Jian-Wu Wang; Hui Guo (Journal of Immunology Research)
Objective. A retrospective analysis of clinical characteristics and immunological manifestations of primary Sjogren’s syndrome (pSS) patients with or without renal involvement was conducted in order to elucidate the potential risk factors of renal damage in pSS and evaluate the condition. Methods. A total of 1002 patients, who fulfilled the 2002 classification criteria for pSS from the Second Affiliated Hospital of Shanxi Medical University, were enrolled in the cross-sectional study. Clinical, immunological, and histological characteristics were compared between pSS patients with and without renal involvement, and potential risk factors of renal involvements in pSS patients were examined by multivariate analysis. Results. Among these pSS patients, there were 162 cases (16.17%) with and 840 cases (83.83%) without renal damage. Serious edema of both lower limbs, interstitial nephritis, and renal tubular acidosis were found in the pSS with renal damage group. Compared with simple pSS patients, the levels of creatinine, cystatin C, and alpha-1-microglobulin (α1-MG) in the pSS with renal damage group were significantly increased. The difference between the two groups was statistically significant (P<0.05). The AUC of the combination of creatinine and α1-MG and creatinine, α1-MG, and creatinine was statistically larger than that of creatinine, and the biomarker of the biggest AUC is the combination of creatinine and α1-MG. Conclusion. The main clinical manifestations of pSS with renal damage were edema of the lower limbs, interstitial nephritis, and renal tubular acidosis. Creatinine and α1-MG are effective indicators for renal function in pSS, which may provide a better understanding for clinical decision-making.